Konsep Deep Learning dalam Perspektif Nilai-Nilai Ki Hajar Dewantara - Ardika Dewa Nugroho; Muhammad Jaatsiy Abdillah (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2026)
This research analyzes the concept of deep learning in education through the philosophical values of Ki Hajar De-wantara. Utilizing a qualitative literature study, it explores the connection between deep learning, Indonesian hu-manistic values, and local wisdom. The findings reveal that Dewantara's "Tri Pusat Pendidikan" (Three Educational Centers) and his three main mottos Ing Ngarso Sung Tuladha, Ing Madya Mangun Karsa, and Tut Wuri Handaya ni are closely aligned with deep learning principles, such as contextual learning, holistic development, and stu-dent independence. The research also identifies challenges in implementing deep learning technology, including risks of dehumanization, the digital divide, and an overemphasis on technical aspects at the expense of values. To address these issues, the study proposes a conceptual framework that encompasses four dimensions: pedagogical, technological, ethical, and socio-cultural. This synthesis of technological advancement and local wisdom offers a fresh perspective on humanistic digital education. The findings contribute both theoretically and practically to educators, technology developers, and policymakers in designing AI-based learning systems rooted in humanistic values.